Habitualisasi Nilai-Nilai Kepemimpinan Transformatif Perspektif Kiai Hasan Mutawakkil ‘Alallah - Fauzi, Ahmad (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2018)
Currently, the development of Islamic education is astonishing in numbers, but the spirit is generally not accompanied by adequate capacity and capability. As the consequence, most Islamic education faces problems and gives rise to negative cycles of unsolved problems. Numbers of research results have suggested that the schools could turn the negative cycles into the positive one, or to transform the Islamic education from low quality of education into good quality schools. It necessitates an ideal leadership through a transformative leadership model. In order to build such leadership, this study aims to nbe an important part to profoundly describe the social values ​​of the kiai leadership as the core values ​​of a transformative leadership using Pierre Bourdieu's social practice theory of social action, between (Habitus x Capital) + Ranah = Practice. Using the above perspective, the internalization of the values ​​referred to be social capital for the kiai to give birth to the model of transformative leadership. Because essentially the above value system is a holistic expression of the role and social actions of kiai that comes from al-Qur'an and al-Hadith as a belief and a basic value in the midst of society to make changes. The habitualization of the above values ​​is an alternative in developing Islamic education, and is seen as the main source and force for change, through the actions and roles of kiai as leaders.